EFFECT OF REHABILITATIVE EXERCISES IN AND OUTSIDE AQUEOUS MEDIUM ON MUSCULAR STRENGTH AND STATIC BALANCE OF THE SEMIMEMBRANOSUS MUSCLES FOR ADVANCED FOOTBALL PLAYERS - Basimshareefsayah, Prof .Dr. Shaima Ali Khamis, Prof .Dr. Maher Abdul Hamza Hardan Alalwani (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Sports injuries are one of the basic problems that hinder the process of progressing at all levels of sports and moving them from one level to another, including football, which results from the injury they stop playing with the team and may be for a long time and thus the team lost important players during the competitions, and the importance of research in preparing exercises inside and outside the water medium lies in the muscular strength and stable balance of the posterior thigh muscles of advanced football players and using them in the future to avoid the occurrence of injury itself. Research problem: Through the personal experience for researchers, they noted that the hamstring muscle injury is one of the most common sports injuries that occur to football players,the researchers attribute the reason for this due to the fact that most players and coaches ignore these injuries with mild symptoms at first and continue training with this injury and some players do not work to strengthen the posterior thigh muscles, so they are susceptible to injury as well as the intense training load, which generates direct effort on these muscles and the result of all these things happen to us, therefore, the researchers decided to study this problem and develop appropriate solutions to it through preparing rehabilitative exercises based on sound scientific foundations to develop the muscular strength and stable balance of the posterior thigh muscles of advanced football players and to benefit from them in the future to avoid the occurrence of the same injury. Research objectives: Prepare rehabilitative exercises inside and outside the aqueous medium for injured posterior thigh muscles for advanced soccer players and to identify the effect of rehabilitative exercises inside and outside the aqueous milieu on muscular strength and stable balance of the hidden thigh muscles of advanced soccer players and using them in the future to avoid the occurrence of the same injury. The researchers followed the experimental approach by designing the two equivalent groups with the pre and post-tests, and the research sample was chosen by the intentional examination method. The sample included a number of injured players and according to the diagnosis by the doctor the specialist and the doctor’s examination with sonar and the medical report of (10) injured players who were divided into (6) the players of the main experiment, (4) the players of the exploratory experiment were divided into two equal groups, and each group (3) of the injured players in the main experiment, while the rest of the members of the research community, who numbered (4) players with the same injury, were excluded as a result of their participation in the exploratory experiment . The researchers reached a set of conclusions, the most important of which are: Rehabilitative exercises inside and outside the aqueous environment have a positive effect on developing muscle strength, balance, and rehabilitative exercises within the aqueous medium have a preference for rehabilitative exercises outside the aqueous medium over the injured posterior thigh muscles in the research sample. In light of these conclusions, the researchers recommended several recommendations, the most important of which are: the necessity of using the water medium in the rehabilitation of the posterior thigh muscles and the rest of the thigh injury (front thigh muscles, connective muscles), the necessity of providing the water medium in rehabilitation and physiotherapy centers, and that the rehabilitation be by a rehabilitation specialist.